2009
DOI: 10.1175/2009mwr3019.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Madden–Julian Oscillation on Summertime Cloud-to-Ground Lightning Activity over the Continental United States

Abstract: Summertime cloud-to-ground lightning strikes are responsible for the majority of wildfire ignitions across vast sections of the seasonally dry western United States. In this study, a strong connection between active phases of the Madden-Julian oscillation (MJO) and regional summertime lightning activity was found across the interior western United States. This intraseasonal mode of lightning activity emanates northward from the desert Southwest across the Great Basin and into the northern Rocky Mountains. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…One unexpected result is that the MJO does not have an important contribution in the lightning activity modulation. Indeed, Abatzoglou and Brown (2009) showed that MJO affects the lightning activity over the continental United States. MJO causes the amplification of the upper-level ridge over the western US and the development of mid-tropospheric instability leading to an enhancement of lightning activity.…”
Section: High Frequency Modesmentioning
confidence: 99%
“…One unexpected result is that the MJO does not have an important contribution in the lightning activity modulation. Indeed, Abatzoglou and Brown (2009) showed that MJO affects the lightning activity over the continental United States. MJO causes the amplification of the upper-level ridge over the western US and the development of mid-tropospheric instability leading to an enhancement of lightning activity.…”
Section: High Frequency Modesmentioning
confidence: 99%
“…[3] The MJO has been shown to modulate a broad range of weather phenomena in the United States, including lower, middle, and upper tropospheric circulation [Seo and Son, 2012;Roundy et al, 2010;Lorenz and Hartmann, 2006]; surface temperature [Zhou et al, 2011;Yao et al, 2011]; daily rainfall [Becker et al, 2011;Jones et al, 2011;Zhou et al, 2011;Donald et al, 2006]; and cloud-to-ground lightning [Abatzoglou and Brown, 2009]. As Rossby waves propagate northeastward [e.g., Wang and Rui, 1990;Waliser, 2006] and downstream [Gottschalck et al, 2010] from anomalous equatorial convection associated with the MJO, the form and shape of the resulting wave train depends strongly on the longitudinal center of the heating [Matthews et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not find any significant annual relationships between summer MEI and the number of lightning strikes (derived from the National Lightning Detection Network) within each ecoregion over the 1990–2009 period. However, subseasonal variability in lightning activity [e.g., Abatzoglou and Brown , ] and lightning busts responsible for widespread fire activity and VLF may be overlooked using seasonal averages. Changes in fire suppression practices [ Marlon et al ., ] and invasive annual grasses [ Balch et al ., ] have also likely modified the potential for VLF and their sensitivity to climate factors over multidecadal time periods.…”
Section: Resultsmentioning
confidence: 99%